Basal cell adenocarcinoma of the maxillary sinus: A case report. (September 2021) - Kojima, Masataka; Ito, Shin; Tou, Miri; Sonoda, Kenji; Yoshikawa, Akihisa; Ohtsuji, Naomi; Ikeda, Katsuhisa; Higo, Ryuzaburo
Basal cell adenocarcinoma is a low-grade malignancy of the salivary glands. Basal cell adenocarcinoma of the minor salivary gland is an extremely rare disease that originates from the maxillary sinus. The histopathological characteristics of basal cell adenocarcinomas are similar to those of basal cell adenomas. However, basal cell adenocarcinomas can be differentiated from basal cell adenomas based on their tendency to invade surrounding tissues. Surgical resection is the first-line treatment for basal cell adenocarcinomas. An 86-year-old man underwent operations for a maxillary sinus tumor twice in our department. The pathological results of the tumor at both times revealed basal cell adenoma. After 4 and 5 years since the last operation, the tumor recurred, and the patient was treated with partial maxillectomy using Weber–Ferguson incision. We observed invasions to the surrounding tissue, and based on immunohistochemical findings, the patient was diagnosed with basal cell adenocarcinoma. Herein, we present an extremely rare case of basal cell adenocarcinoma arising from the maxillary sinus, in detail.